High-Shear Wet Granulation of SMEDDS Based on Mesoporous Carriers for Improved Carvedilol Solubility - Mila Kovačević; Ilija German Ilić; Katarina Bolko Seljak; Alenka Zvonar Pobirk (MDPI AG, 2022)
Mesoporous carriers are a convenient choice for the solidification of self-microemulsifying drug delivery systems (SMEDDS) designed to improve the solubility of poorly water-soluble drugs. They are known for high liquid load capacity and the ability to maintain characteristics of dry, free-flowing powders. Therefore, five different mesoporous carriers were used for the preparation of carvedilol-loaded SMEDDS granules by wet granulation methods-in paten (manually) and using a high-shear (HS) granulator. Granules with the highest SMEDDS content (63% and 66% of total granules mass, respectively) and suitable flow properties were obtained by Syloid® 244FP and Neusilin® US2. SMEDDS loaded granules produced by HS granulation showed superior flow characteristics compared to those obtained manually. All SMEDDS granules exhibited fast in vitro release, with 93% of carvedilol releasing from Syloid® 244FP-based granules in 5 min. Upon compaction into self-microemulsifying tablets, suitable tablet hardness and very fast disintegration time were achieved, thus producing orodispersible tablets. The compaction slightly slowed down the carvedilol release rate; nevertheless, upon 1 h (at pH 1.2) or 4 h (at pH 6.8) of in vitro dissolution testing, the amount of released drug was comparable with granules, confirming the suitability of orodispersible tablets for the production of the SMEDDS loaded single unit oral dosage form.